(3eSDhdjGJ hELQGAGJ GdeQGLY aj GdJbQjQ Yf GdZT hGdeeGQSGJ GdeMGSHjI GdNGWFI (B/s - (3dWaj, Cejf GdSjO CMeOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2005)
(3eSDhdjGJ hGLQGAGJ GdeQGLY(B- (3WHjYI hUhQ GdeeGQSGJ GdeMGSHjI GdNGWFI hGdZT(B- (3eQGMd JWhQ OhQ hGLQGAGJ eQGbHj GdMSGHGJ aj GdJbQjQ Yf GdZT(B- (3eSDhdjGJ hGLQGAGJ GdeQGLY GdGNQi Yf Jbjje hGcJTGa GdJUQaGJ ZjQ GdbGfhfjI hedGFeI aQU GSJeQGQjI GdTQcI GdeSDhdjI GdbGfhfjI ddeQGLYjf(B- (3JWhjQ OhQ hGLQGAGJ GdeQGLY aj GdJbQjQ Yf GdZT HGSJNOGe fXe OYe GdbQGQ(B- (3eSDhdjGJ hELQGAGJ GdeQGLY Yf GdZT hGdGNWGA aj GdHjFI GdeUQjI(B.s
(3eQGLY U(B.404s
Keywords: (3GdELQGAGJ GdEOGQjIs; (3eQGLYI GdMSGHGJs